Optimizing Student Learning Quality in Phase C Catholic Religious Education Grade V through a Behavioral Learning Model at SDN 064977 Medan Tembung - Sihombing, Irfan Vinsensius; Sihotang, Din Oloan (Jurnal Penelitian Medan Agama, 2025)
This study aims to optimize the learning quality of Catholic Religious Education Phase C Grade V students through the Behavioral learning model at SDN 064977 Medan Tembung. The research method used is classroom action research (CAR) with two cycles. The research subjects consisted of six fifth-grade students evaluated based on learning enthusiasm, creativity, and academic skills, which include cognitive, affective, and psychomotor aspects. Data were collected through observation, and evaluation tests. The results showed that before implementing the Behavioral model, the learning mastery rate was only 33%. After implementation in Cycle I, mastery increased to 83%, and in Cycle II, it reached 100%. The Behavioral learning model, which focuses on stimulus provision, student responses, reinforcement, behavior shaping, and evaluation and generalization, proved effective in enhancing learning quality. Thus, this model can be recommended as a strategy to improve student motivation and learning outcomes in Catholic Religious Education.